Institutional change and the evolution of the regulatory state: evidence from the Swiss case. (June 2014) - Maggetti, Martino
This article examines institutional change in a case that was expected to be particularly resilient but showed considerable structural transformation: the institutionalization of the regulatory state in Switzerland. This process is illustrated through the establishment of independent regulatory agencies (IRAs) in four areas: banking and finance; telecommunications; electricity; and competition. The theoretical framework developed by Streeck, Thelen and Mahoney is used to explore hypotheses about the modes of institutional change, with the methodology of diachronic within-case study. Results confirm only partially the expectations, pointing to layering and displacement as the prevalent modes of change. The concluding part discusses the type and the direction of change as additional explanatory factors. Points for practitioners: This article examines the institutional development of the regulatory state in Switzerland through the establishment of independent regulatory agencies (IRAs). Different modes of change are illustrated through the analysis of the processes leading to agencification in four areas: banking and finance; telecommunication; electricity; and competition. Results suggest that the dynamics of re-regulation follow a quite different logic compared to the general trend towards liberalization. What is more, the empirical analysis indicates that independent regulatory agencies are mostly created by importing exogenous models in the case of the 'positive' reform of previously self-regulated sectors, while they are established along existing institutional arrangements when reforming former state-owned enterprises or publicly regulated sectors.